KAJIAN KOMPOSISI KIMIA SNACK BARS DARI BERBAGAI BAHAN BAKU LOKAL : SYSTEMATIC REVIEW STUDY OF THE CHEMICAL COMPOSITION OF SNACK BARS FROM VARIOUS LOCAL RAW MATERIALS : SYSTEMATIC REVIEW - Mayestika S. D. Taula’bi’; Yoakhim Y.E. Oessoe; Maria F. Sumual (AGRI-SOSIOEKONOMI, 2021)
Snack bars is one of the commercial food products found in the market but this product mostly still use imported raw materials such as soybeans and wheat. Research on the use of local food as raw material for making snack bars is currently in great demand considering that Indonesia has abundant potential agricultural to be optimized in supporting food diversification efforts. This study aims to make an inventory of the types of local raw materials that have been used in the manufacture of snack bars, to record and to study the types binders of snack bars and to evaluate the chemical composition of local raw material snack bars. This research was made with a systematic review design with the PRISMA method. From the results of the systematic review conducted, it was found that local raw materials for cereals, nuts, fruits, vegetables and local tubers can be combined to be used as raw material for making snack bars. Several types of binders that have been used in the manufacture of snack bars are cornstarch, tapioca, sugar, eggs, and also maltodextrin. The evaluation results of the chemical composition of local raw material snack bars, namely having water content ranged from 2.28% - 53.4%, carbohydrate content 27.3% - 86.66%, fat content 8% - 34.46%, protein content 3.49% - 17.61%, and total calories 294.19 kcal/100 g - 552.71 kcal/100 g which is influenced by several factors, namely the use of various raw materials, additional materials used, and the processing of snack bar products